Physiological endocrinology and causes of disorders of the menstrual cycle - Eliza Haryanti; Legiran (Science Midwifery, 2023)
The menstrual cycle is the result of a complex interaction between the hormonal system and the body's organs, namely the hypothalamus, pituitary, ovaries and uterus. Regular menstrual cycle is an indicator of women's reproductive health, changes in the menstrual cycle can be associated with ovarian-thyroid dysfunction and pituitary axis. This article aimsto understand the role of endocrinology in the process of the menstrual cycle as well as review the currently available literature on the causes of disorders of the menstrual cycle.The method used is Systematic Literature Review using the Preferred Reporting Items for Systematic Reviews (PRISMA) flow by collecting articles, according to those obtained from the PubMed database, Wiley Online Library, Science Direct and Cochrane, with the keywords "Menstrual cycle, hormone disruption, gynecological disease , and endocrinology” from the results of the analysis, 6 articles were selected that met the criteria. The conclusion ismany factors influence the occurrence of disturbances in the menstrual cycle that can affect reproductive health, including diabetes, night shift work schedules, nutritional intake, smoking habits, as well as psychological stress and anxiety during the pandemic due to the Covid-19 disease and vaccine administration.